Conservation of seeds of Crimean endemic species Alyssum calycocarpum Rupr. (Brassicaceae) and Anthyllis biebersteiniana Popl. (Fabaceae) in liquid nitrogen (–196° C) - Arapetyan, E.R. (Український ботанічний журнал, 2013)
Preservation ex situ of the seeds of Alyssum calycocarpum Rupr.
(Brassicaceae) and Anthyllis biebersteiniana Popl. (Fabaceae),
species endemic to the Crimean flora, has been studied using
modern cryotechnique. The seeds survived after having been exposed to ultra low temperature (–196°C) during a month. Зберігання ex situ насіння Alyssum calycocarpum Rupr. (Brassicaceae) і Anthyllis biebersteiniana Popl. (Fabaceae), ендемічних видів флори Криму, досліджували з використанням сучасного методу кріотехнології. Насіння не втратило життєздатності після перебування його протягом місяця у рідкому азоті. Хранение ex situ семян Alyssum calycocarpum Rupr. (Brassicaceae) і Anthyllis biebersteiniana Popl. (Fabaceae), эндемических видов флоры Крыма, исследовали с использованием современной криотехнологии. Семена сохранили жизнеспособность после хранения их в течении месяця в жидком азоте.